Surgical removal of entrapped guidewire fragment following direct circumflex artery angioplasty and stenting - Domaradzki, Wojciech; Sanetra, Krzysztof; Skwarna, Bartosz; Król, Marek; Kuczera, Małgorzata; Cisowski, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
We present a case of a 64-year-old man with coronary artery disease, who underwent a percutaneous coronary intervention of the circumflex artery. As the guidewire was being withdrawn from the target vessel, it became entrapped by the structure of the previously implanted stent. Attempts to retrieve the foreign body were unsuccessful. Changes in electrocardiogram were observed during the procedure, and the level of cardiac biomarkers increased within the next 24-hours. The patient was admitted to the Cardiac Surgery Department. Remnants of the foreign body were removed under visual control using extracorporeal circulation, and coronary artery bypass grafting was performed. Treatment options and outcomes are discussed.